Formulation and characterization of eprosartan mesylate and β-cyclodextrin inclusion complex prepared by microwave technology - Abdul Ahad; Yousef A. Bin Jardan; Mohd. Zaheen Hassan; Mohammad Raish; Ajaz Ahmad; Abdullah M. Al-Mohizea; Fahad I. Al-Jenoobi (Taylor & Francis Group, 2022)
The goal of this work was to improve the aqueous solubility and dissolution rate of eprosartan mesylate by preparing inclusion complex of drug with β-cyclodextrin (β-CD) by microwave technique. In order to determine the solubility of eprosartan, phase solubility was determined and dissolution study was also conducted. Further, analytical techniques for instance, particle size distribution, differential scanning calorimetry, powder X-ray diffraction, scanning electron microscopy, Fourier-transform infrared spectroscopy, and nuclear magnetic resonance spectroscopy were used for the characterization of inclusion complex. In addition, the binding pattern of eprosartan with the β-CD was investigated by molecular modeling study. Phase solubility study revealed that approximately 4.48 folds improvement in the solubility of drug was noted with β-CD (10 mM). The estimated stability constant (Kc) values for eprosartan:β-CD binary mixture was found to be 280.78 M-1. The prepared inclusion complex of drug with β-CD presented better drug release profile (62.96 ± 2.01% in 1 h) as compared to their physical mixture (41.41 ± 1.77% in 1 h) or drug per se (29.97 ± 3.13%). The inclusion complex demonstrated different features and properties from pure drug, and we inferred that this could be due to the inclusion of drug into cyclodextrin cavity that confirmed by different analytical method. Molecular modeling study demonstrated a good affinity of eprosartan to entangle to β-CD. The outcomes have shown that guest molecule has many significant interactions with the host molecule. These observations are very interesting and may be a valuable approach to improve the solubility and in turn the bioavailability of eprosartan.